2016
DOI: 10.1103/physrevb.94.075112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic correlation and magnetic frustration inLi2VOSiO4andVOMoO4

Abstract: Li 2 VOSiO 4 and VOMoO 4 have been proposed as realizations of the frustrated two-dimensional J 1 -J 2 quantum Heisenberg model. In this work, in order to test this picture, we study their electronic and magnetic properties by using the local-density approximation + dynamical mean-field theory method. We calculate the magnetic linear response function starting from material-specific Hubbard models and systematically map our results onto those from generalized quantum Heisenberg models. We obtain the effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The magnetic response function for VOMoO 4 is shown in Figure 15. Our calculations [25] support a weak frustration picture for both vanadates, with a small but non-negligible degree of three-dimensionality, which fully account for the three-dimensional magnetic order reported in experiments. Although weak, the frustration is large enough to explain the partial reduction of the ordered magnetic moments measured via neutron scattering experiments [69,70].…”
Section: Are Layered Vanadates 2-dimensional Frustrated Systems?supporting
confidence: 56%
See 1 more Smart Citation
“…The magnetic response function for VOMoO 4 is shown in Figure 15. Our calculations [25] support a weak frustration picture for both vanadates, with a small but non-negligible degree of three-dimensionality, which fully account for the three-dimensional magnetic order reported in experiments. Although weak, the frustration is large enough to explain the partial reduction of the ordered magnetic moments measured via neutron scattering experiments [69,70].…”
Section: Are Layered Vanadates 2-dimensional Frustrated Systems?supporting
confidence: 56%
“…Finally, we use the Filon-trapezoid method to minimize the time required to perform the Fourier transform to Matsubara space as well as an extrapolation scheme to sum up Matsubara frequencies. This approach is implemented in our generalized HF-QMC solver [25].…”
Section: Generalized Linear-response Functionsmentioning
confidence: 99%
“…The later studies of the solid solutions Li 2 V 1−x OTi x SiO 4 (for 0 ≤ x ≤ 0.2) by means of 7 Li and 29 Si NMR, muon spin relaxation (µSR), as well as magnetization [26] revealed that the ratio |J 2 /J 1 | decreases with x, and the magnetic ordering temperature decreases with reducing the spin stiffness [24] by a factor of approximately (1−x) 2 . In contrast to the case of Li 2 VOXO 4 (X = Si, Ge), the J 1 and J 2 exchanges compete in the S = 1/2 (V 4+ ) QHAF system, VOMoO 4 , [27,28] which orders at a markedly higher temperature (~ 42 K) and demonstrates a structural distortion. It is worthwhile to note that theoretical calculations [16,28] predict a quite strong interlayer exchange for both Li 2 VOXO 4 (X = Si, Ge) and VOMoO 4 .…”
Section: Introductionmentioning
confidence: 86%
“…It was shown that super-exchange yields a Fig. 4 Quasiparticles and Hubbard bands in the doped 2D Hubbard model (square lattice) with dispersion ε(k) = −2t(cos k x + cos k y ) + 4t cos k x cos k y , obtained with the dynamical mean-field theory approach [53,54]. The special points are Γ = (0, 0, 0), X = (0, π/a, 0), M = (π/a, π/a, 0), and Z = (0, 0, π/a).…”
Section: It Is Not All About the Gapmentioning
confidence: 99%
“…Calculations were performed for U = 7 eV, t = 0.4 eV, 290 K. The quantum impurity solver adopted is the Hirsch-Fye quantum Monte Carlo [55] method in the implementation of Ref. [53]. The number of holes is indicated with x large transition temperature, but is not sufficient to explain alone the persistence of distortions till very high temperatures; in the case of ionic systems such as KCuF 3 , a new mechanism was identified [46], with the Born-Mayer repulsion playing a key role in determining the actual experimental structure (Fig.…”
Section: It Is Not All About the Gapmentioning
confidence: 99%